The last native Manx Gaelic speakers: the final phase: "full" or "terminal" in speech? - Broderick, George (Studia Celtica Fennica, 2017)
This article looks at the last fifteen native Manx speakers who were recorded most by various bodies, e.g. Irish Folklore Commission (1948), Manx Museum (1950-52), and Yn Cheshaght Ghailckagh (Manx Language Society) (1951-53), and individuals (Carmody (1949, Wagner (1950), Jackson (1950-51), and their comments on the speakers, we look also at their family baclground as to how they came to acquire Manx and whether they learned it as a full or semi-speaker. After assessing all aspects a conclusion is reached.